2018
DOI: 10.1161/jaha.117.007942
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Coronary Artery Spasm Diagnosis in Patients With Early Repolarization Syndrome

Abstract: BackgroundPreviously described patients with early repolarization syndrome (ERS) may have experienced silent coronary artery spasm (CAS) because the diagnosis of CAS was mainly based on symptoms or coronary angiography findings, without performing a spasm provocation test. This study investigated the significance of CAS diagnosis and evaluated the incidence of silent CAS in patients with possible ERS (ie, idiopathic ventricular fibrillation [VF] and inferolateral J wave).Methods and ResultsThe study included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Coronary vasospasm, while a recognized cause of cardiac arrest, may not be picked up clinically at presentation. 292 Ergonovine or acetylcholine challenge has been proposed as a Class 1 indication by recent guidelines 293 and was employed selectively in the CASPER experience. 216 Hyperventilation has also been used as a diagnostic test.…”
Section: Investigation Of Sudden Cardiac Arrest Survivors: Provocative Testingmentioning
confidence: 99%
“…Coronary vasospasm, while a recognized cause of cardiac arrest, may not be picked up clinically at presentation. 292 Ergonovine or acetylcholine challenge has been proposed as a Class 1 indication by recent guidelines 293 and was employed selectively in the CASPER experience. 216 Hyperventilation has also been used as a diagnostic test.…”
Section: Investigation Of Sudden Cardiac Arrest Survivors: Provocative Testingmentioning
confidence: 99%
“…Coronary vasospasm, while a recognized cause of cardiac arrest, may not be picked up clinically at presentation 292 . Ergonovine or acetylcholine challenge has been proposed as a Class 1 indication by recent guidelines 293 and was employed selectively in the CASPER experience 216 .…”
Section: Investigation Of Sudden Cardiac Arrest Survivorsmentioning
confidence: 99%
“…Finally, a total of eight studies were included in the meta‐analysis. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 The study selection process is shown in Figure S2 (see Figure and Supplemental Content, which illustrates the flow diagram of study selection).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of eight studies were included in the metaanalysis. [15][16][17][18][19][20][21][22] The study selection process is shown in Figure S2 (see All the selected studies were retrospective cohort studies, which were published between 2011 and 2020, with sample sizes ranging from 34 to 458 patients and a total of 1761 patients. All patients were from South Korea and Japan.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%